AB1311-HPR RHEUMATIC AND MUSCULOSKELETAL DISEASES MANAGEMENT TOOL HELPS TO IMPROVE TREAT-TO-TARGET THERAPY AND PATIENTS' ADHERENCE TO TREATMENT. (2nd June 2020) - Wu, P.; Li, W.; Zeng, H.; Lian, F.
Abstract : Background: Many of the rheumatic and musculoskeletal diseases (RMD) are long term, painful, and function affecting, which takes both the doctors and patients a lot of time and effort. The number of Rheumatologists are not sufficient for the huge population of RMD patients in China. The doctor patient ratio is as low as 1:1000. Relatively inadequate medical resources, traffic inconvenience in rural area, and patients' insufficient understandings of the RMD may cause delayed medical intervention and poor prognosis. Effective RMD patient management tools which provide disease monitoring and enough doctor-patient communication is essential to improve the patients' adherence to treatment. We designed an RMD management app according to the social, cultural and economic situation of Chinese patients, which helps to facilitate shared decision making and relieve the pressure of insufficient medical resources. Objectives: We aim to investigate the effect of RMD patient management app on treat-to-target therapy and patients' adherence and satisfaction to treatment. Methods: An observational survey was administrated using a RMD patient management app. The app was designed and improved by Rheumatologist, orthopedics, nurses, patients, and app technical experts. Patients were offered with a questionnaire in regard to satisfaction with the app and their attitudes about the disease. General therapeutic principles, rehabilitation exercise videos and follow-up information were distributed through the app. Warning signals were sent whenever there was a flag sign of exacerbation. The demographic and clinical data, social and economic status, and drug retention rates of the patients were documented. The survey was designed by clinical experts from relevant departments and developed by both doctors and patients. Results: All patients were supervised by the rheumatologist and orthopedist when using the app. In all the patients included, there were cases of rheumatoid arthritis (35.3%), osteoarthritis (32.4%), ankylosing spondylitis (26.5%), and other chronic arthritis (5.8%). The mean age 38.5±15.8 years old, with 52.9% male and 47.1% female. Most of the patients (85.3%) believed that the app was helpful. Young patients were more likely to respond to the survey than older patients. Some patients (79.4%) had increased compliance because the app offered more chances to communicate with the doctors, which increase their understanding and confidence about the disease. Three patients received flag signs of exacerbation much earlier than they could get to the hospital. From the feedback of the patients, we realized that the patient would like to have more information to keep them from stepping on the trap of false advertisement for therapy (which is very commonly seen in China). Conclusion: RMD patient need to manage disease activity, daily function and mental state. Insufficient medical resources and patients' knowledge about the disease may lead to poor adherence and prognosis. RMD patient management tool on app was a feasible and cost-effective approach for data collection and patient education. The app increased treat-to-target therapy and patients' adherence to treatment. References: None. Disclosure of Interests: None declared